The Impact of Human Development Components on Poverty Reduction: A Comparative Analysis Across Provinces in Java, Indonesia Using Linear Mixed Models - Abdullah Said; Moch. Zainal Mustofa; Fathir Achmad Sulaiman (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study examines the impact of Human Development Index (HDI) components: education, health, and expenditure on poverty levels across provinces in Java, Indonesia. Using secondary data from the Indonesian Bureau of Statistics and applying a Linear Mixed Model approach, this research captures both cross-sectional and temporal variations across regions. The findings reveal that education and expenditure have a significant negative effect on poverty, indicating that improvements in human capital and economic capacity contribute to poverty reduction. Conversely, the health index shows a positive and significant relationship with poverty, suggesting a non-linear and complex interaction influenced by structural and demographic factors. The model demonstrates moderate explanatory power, with a pseudo R-squared value of 0.479, indicating that nearly half of the variation in poverty can be explained by the selected variables. These results highlight that poverty is a multidimensional phenomenon requiring integrated policy interventions. The study contributes to the literature by decomposing HDI into its components and employing a multilevel analytical approach to better understand regional disparities in development outcomes.